H∞ Filtering of 2d Linear Fm Ii Model Delayed Systems - Acosta-Barbosa, K; Zoulagh, T (EDP Sciences, 2023)
The aim of this study is to address the challenge of H∞ filtering for 2-D systems with time delays. We will employ the well-known Fornasini-Marchesini state model with delay to mathematically describe these 2-D systems. Our objective is to develop a full-order filter that not only ensures the asymptotic stability of the expanded system but also maintains H∞ performance. Our approach will rely on Linear Matrix Inequalities (LMIs) to establish the conditions for the filter’s existence and convert the filter design problem into a convex optimization problem. Finally, we conclude with an illustrative example to demonstrate the effectiveness of the proposed filter design. © The Authors, published by EDP Sciences.